Peningkatan Motivasi Belajar Pada Anak-Anak Panti Asuhan Aisyiyah Melalui Video Motivasi Dan Pohon Harapan - Salsabila Ilza, Rizka; Rahmi, Lailatur (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2025)
Every human being has the hope of having a bright future, with that, everyone must have ideals or desires to determine life in the next phase. Likewise with the children of the Aisyiyah Bukittinggi orphanage who have the motivation to be able to achieve their ideals. Learning motivation is influenced by the child's attitude towards learning and the learning motivation possessed by the child himself. One way to increase learning motivation is with motivational videos and trees of hope. This study is based on the phenomenon of low learning motivation of children in orphanages. The purpose of the study: 1) To determine the increase in learning motivation in children at the Aisyiyah orphanage through motivational videos, 2) To increase learning motivation in children at the Aisyiyah orphanage through trees of hope. The type of research used in this study is mixed methods. The sample in this study were children at the Aisyiyah orphanage at junior high and senior high school levels. Data collection was carried out through observation, questionnaires and interviews. Furthermore, the collected data were analyzed using quantitative data analysis techniques: validity test and reliability test, while qualitative data were analyzed using the method developed by Miles and Suherman, namely data reduction, data presentation and drawing conclusions. The results of the study showed: 1) There was an increase in the learning motivation of the children at the Aisyiyah orphanage by 30.51 points from an average pretest score of 56.90 points to 87.41 points posttest score, 2) The children at the Aisyiyah orphanage became more motivated to learn after being given an understanding of the tree of hope